2019
DOI: 10.1080/01652176.2019.1643051
|View full text |Cite
|
Sign up to set email alerts
|

Animal mesenchymal stem cell research in cartilage regenerative medicine – a review

Abstract: Healing of articular cartilage is a major clinical challenge as it also lacks a direct vasculature and nerves, and carries a limited number of resident chondrocytes that do not proliferate easily. Damaged articular cartilages are usually replaced by fibrocartilages, which are mechanically and structurally weaker and less resilient. Regenerative medicine involving stem cells is considered to have a definitive potential to overcome the limitations associated with the currently available surgical methods of carti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 176 publications
(382 reference statements)
0
22
0
Order By: Relevance
“…Although the ovine knee cartilage differs in thickness to human cartilage (0.7−1.7 mm and 2.35 mm, respectively), it provides a close match regarding mechanical properties for preclinical studies (Frisbie et al, 2006;Chu et al, 2010;Mclure et al, 2012). Tissue engineering approaches including different cell sources (as MSCs or chondrocytes) have been widely tested in the sheep for chondral/osteochondral defects (Lo Monaco et al, 2018;Gugjoo et al, 2019). Cells can also be applied with scaffolds of different nature to improve and support regeneration (Chitosan, type I/III collagen, b-TCP, collagen hydrogels) (Bernstein et al, 2013;Sanz-Ramos et al, 2014;Dias et al, 2018).…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ovine knee cartilage differs in thickness to human cartilage (0.7−1.7 mm and 2.35 mm, respectively), it provides a close match regarding mechanical properties for preclinical studies (Frisbie et al, 2006;Chu et al, 2010;Mclure et al, 2012). Tissue engineering approaches including different cell sources (as MSCs or chondrocytes) have been widely tested in the sheep for chondral/osteochondral defects (Lo Monaco et al, 2018;Gugjoo et al, 2019). Cells can also be applied with scaffolds of different nature to improve and support regeneration (Chitosan, type I/III collagen, b-TCP, collagen hydrogels) (Bernstein et al, 2013;Sanz-Ramos et al, 2014;Dias et al, 2018).…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…In addition, arthroscopic evaluation is possible in the sheep due to the size of their stifle joints. Therefore, the ovine species is the most commonly used large animal model in orthopedic research including studies on: cartilage repair ( Music et al, 2018 ), meniscal repair ( Hurtig et al, 1998 ; Tytherleigh-Strong et al, 2005 ), osteochondral tissue engineering ( Sanjurjo-Rodriguez et al, 2017 ), tendon defects ( Crovace et al, 2008 ; Martinello et al, 2013 ), osteoarthritis ( Oakley et al, 2004 ; Gugjoo et al, 2019 ), and osteoporosis ( Dias et al, 2018 ) among the others.…”
Section: Sheep As Animal Modelsmentioning
confidence: 99%
“…Although the literature is full of studies that favor MSCs immuno-modulatory effects but many studies have failed to see immuno-privileged and/ immuno-modulatory effects of the cells [ 3 , 9 , 15 , 122 ]. Many studies have shown that MSCs carry a number of receptors that can interact with T-cells.…”
Section: Conflicting Research Reportsmentioning
confidence: 99%
“…The controlled application of such cells may be expected to do wonders in the field of therapeutics and regenerative medicine [ 2 , 4 - 7 ]. However, limited understanding of the cellular physiology and effects of the microenvironment restricts their definitive therapeutic applications [ 8 , 9 ]. Among various stem cell types, Mesenchymal Stem Cells (MSCs) are mostly considered for preclinical and/ or clinical trials [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have been described in laboratory, domestic and wild animal species (reviewed by Gugjoo et al 2019a). Equine MSCs, derived from tissues such as bone marrow (Fortier et al 1998), adipose tissue (Vidal et al 2007;Shojaee et al 2019), endometrium (Corradetti et al 2014;Rink et al 2017;Cabezas et al 2018), hair follicles (Michler et al 2018), synovial fluid and membrane (Prado et al 2015), amniotic membrane (Corradetti et al 2014), umbilical cord wall and blood (Koch et al 2007;Cremonesi et al 2008;Alizadeh et al 2018;Merlo et al 2019), have also been investigated.…”
Section: Introductionmentioning
confidence: 99%